2022
DOI: 10.1371/journal.pone.0267624
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant properties of bee propolis and an important component, galangin, described by X-ray crystal structure, DFT-D and hydrodynamic voltammetry

Abstract: Propolis is produced by honeybees and used to seal their hives for defensive purposes and has been used in ethnopharmacology since ancient times. It is a lipophilic material containing a large collection of naturally produced plant organic molecules, including flavonoids. The flavonoid galangin is consistently found in propolis, independent of the hive geographical location and its X-ray crystal and molecular structure is reported. The antioxidant scavenging of superoxide by galangin and propolis is here prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
3
13
1
Order By: Relevance
“…A recent study by us has shown the scavenging of superoxide by the flavonoid galangin [ 25 ]. As seen with the coumarin earlier described, a straightforward SOD action is observed when the first attack of superoxide occurs on galangin H3 and is shown in Scheme 1 below.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study by us has shown the scavenging of superoxide by the flavonoid galangin [ 25 ]. As seen with the coumarin earlier described, a straightforward SOD action is observed when the first attack of superoxide occurs on galangin H3 and is shown in Scheme 1 below.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative initial π-π approach involving one aromatic ring of galangin and superoxide was also explored and is shown in Scheme 2 The original study [ 25 ] has a typographical error whereby Scheme 1 and Scheme 2 are identical. The correct Scheme 1 is shown in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations